1987
DOI: 10.1159/000461670
|View full text |Cite
|
Sign up to set email alerts
|

5-Day Storage of Human Platelet Concentrates in 30 ml of Plasma or Artificial Medium

Abstract: Optimal conditions for the storage of platelet concentrates were studied by changing 5 environmental parameters: bag composition (PL 146 vs. PL732), volume of plasma (60 vs. 30 ml), anticoagulant (CPDA^-1 vs. heparin), nutrient (glucose vs. fructose) and medium (plasma vs. artificial medium). A full bilevel factorial study was conducted to evaluate each variable alone and in combination with the other variables for their effects on platelet aggregation and release in response to single and pairs of stimuli. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Other artificial media are under devel opment by several investigators [17][18][19][20] in a similar effort to provide an alternative to the storage of platelets in plasma. One of the direct benefits of the storage in a nonplasma medium may be derived from the removal of plasma com ponents which could lead to the generation of potent plate let agonists such as thrombin, plasmin, or C3a [1,13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Other artificial media are under devel opment by several investigators [17][18][19][20] in a similar effort to provide an alternative to the storage of platelets in plasma. One of the direct benefits of the storage in a nonplasma medium may be derived from the removal of plasma com ponents which could lead to the generation of potent plate let agonists such as thrombin, plasmin, or C3a [1,13,14].…”
Section: Discussionmentioning
confidence: 99%
“…The results this study confirms that lower volumes result in undesirable lower pH than higher final volumes. In another study Fasola (13) reported the mean volume was considerably low 18.52ml compared to (12) reported a mean of 62.30±22.68 ml. This study also demonstrates that Haemoglobin (Hb) and platelet counts can form an integral part of a rapid, simple and practical method for validation of collection, processing and storage procedures that is useful for routine quality monitoring and pre-release testing of platelet concentrates.…”
Section: Discussionmentioning
confidence: 80%
“…After the second spin 3800 rpm for 9 minutes yielding the platelet concentrate, 83/87 (95.4%) had the required platelet count, (≥450 cells/ml) mean±SD was 783.813±232.24 and concentrate volume (40-70 ml). In a study by Fasola (13) , the mean volume was considerably low (18.52mls) whereas Singh reported a mean of 62.30±22.68 ml. NBTS set minimum volume at 60ml whereas AABB do not have a specified minimum volume.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Certainly, red cell storage studies showed the di(2-ethylhexyl) phthalate plasticizer helps maintain red cell viability during storage. 27,28 In vitro platelet assays suggest that the storage bag [29][30][31][32] and even the method of bag sterilization 33 may affect platelet quality during storage. When Terumo BCT platelets were stored in Haemonetics CLX bags, there were clear improvements in poststorage platelet viability, but the results may still not be as good as Haemonetics platelets stored in Haemonetics CLX bags (Table 3).…”
Section: Discussionmentioning
confidence: 99%